COVID-19: DAMPAK TERHADAP HARGA SAHAM SYARIAH DI ASEAN - Vivi Indah Bintari; Deasy Lestary Kusnandar (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this study was to examine the differences in Sharia stock prices before and after the announcement of the first case of COVID-19 in ASEAN. The population in this study were all countries that are members of ASEAN using purposive sampling method so that a sample of 3 countries was obtained, namely Indonesia (JII), Malaysia (FTSE HIJRAH) and Thailand (SETS). The method used in this research is an event study using paired sample t-test. Based on the test results, it is known that there are significant differences in the stock index JII ,FTSE HIJRAH, SETS before and after the announcement of the first case COVID-19 case in ASEAN.